Determinan Faktor Rendahnya Kepemilikan Jamban Keluarga dengan Regresi Logistik di Desa Penen, Kabupaten Deli Serdang, Sumatera Utara - Novrika Silalahi; Elmina Tampubolon (Inferensi, 2022)
Towards 2025, health in Indonesia is moving towards having all citizens have basic sanitation or community-based total sanitation activities. With this program it is very important to support the importance of programs to increase awareness of family latrine ownership. In Deli Serdang Regency, in the Biru-Biru District, Penen Village is one of the villages whose residents income from agricultural sector has 40% of the family’s latrines. This percentage figure is a small number. For this reason, this study aims to determine the factors that influence low family latrine ownership and determine the biggest factor for low family latrine ownership by means of multivariate analysis, namely logistic regression. Logistic regression is a regression that has special characteristics from linear regression analysis which has the same goal of predicting value. Logistic regression is widely used in the application of the causal factors of several variables, to analyze the relationship of one or more independent variables with a dependent variable that is binary or dichotomous. The variables used in this study are knowledge, economic status, attitudes, behavior, and the role of health workers, to find the factors that cause low family latrine ownership in Penen Village. The research design used cross sectional with a sample of 76 heads of families, with random sampling. The results showed that the variable knowledge (p-value = 0,000), economic status (p-value = 0.001), attitude (p-value = 0,008), behavior (p-value = 0,008), and the role of health workers (p-value = 0,03). The final result of the logistic regression, the variable which is the biggest factor influencing the low family latrine ownership is knowledge with an Odd Ratio of 80,947. The probability value (p) is 0.0038 or 0.38% with the regression model equation formed, namely Y = -17,719 + 4,394 (Knowledge) + 2,272 (Attitude) + 1,34 (Behavior) + 4,14 (Role of Health Workers)